Extreme waves in the southern Baltic Sea - Wojciech Sulisz; Maciej Paprota; Anna Reda (Ciencias Marinas, 2016)
Freak waves are unique phenomena that appear unexpectedly on the ocean surface. These waves are not only a danger to fishermen and yachtsmen, but are also capable of damaging large vessels and offshore and coastal structures. The available field measurements that provide insight into the origin and physics of freak waves are very limited. The main objective of the present study was to analyze a unique set of wave data comprising 19,025 wind-wave records from the southern Baltic Sea to provide information on the occurrence, parameters, and prevailing conditions of the formation of freak waves. The complex nature of freak waves was investigated by obtaining spectral and statistical parameters of freak-wave-prone sea states using a wide set of tools. The study revealed a large number of freak-type waves, including waves over 12 m high. The study indicates that these hazardous waves may even exceed 20 m during severe storms in the Baltic Sea. Multi-point wind-wave measurements are needed to provide more information about the physics of freak waves and to eventually develop a prediction or warning system to avoid casualties.